How people with dementia perceive a therapeutic robot called PARO in relation to their pain and mood: A qualitative study. Issue 3 (2nd December 2019) - Pu, Lihui; Moyle, Wendy; Jones, Cindy
Abstract: Background: Interacting with social robots, such as the robotic seal PARO, has been shown to improve mood and acute pain for people with dementia. Little attention has been paid to the effect of PARO on people with dementia and chronic pain. Objective: To explore how people with mild to moderate dementia and chronic pain perceive PARO as an alternative intervention to manage their pain and mood. Design: A descriptive qualitative approach nested within a pilot randomised controlled trial. Methods: Participants with dementia and chronic pain were recruited from three residential aged care facilities. They interacted with PARO for 30 min, 5 days a week over a 6‐week period. A sample of 11 participants completed individual semi‐structured interviews at the end of the intervention. Data were collected from January 2018–January 2019. Inductive thematic analysis was undertaken. Reporting of findings followed the COREQ checklist. Results: Four themes emerged from the data: (a) perceptions of PARO; (b) therapeutic effects of PARO; (c) limitations of PARO; and (d) programme improvement. Residents with dementia expressed positive attitudes towards the use of PARO and acknowledged the therapeutic benefits of PARO on mood improvement and relaxation for pain relief but also mentioned the limitations of its weight, voice and characteristics. Residents' responses could also fluctuate during the intervention process, and individual preferences need to be considered. Conclusions: The PARO intervention is a promising intervention to improve positive emotion, and there is some anecdotal evidence that pain may be decreased from the perspectives of people living with chronic pain and dementia. Relevance to clinical practice: Long‐term care staff may incorporate PARO therapy into daily dementia care. Understanding of individual's preferences may enhance the implementation of PARO for pain management in this group.